Fast Clearance of the SARS-CoV-2 Virus in a Patient Undergoing Vaccine Immunotherapy for Metastatic Chordoma: A Case Report - Pastor, Danielle M.; Lee-Wisdom, Katherine; Arai, Andrew E.; Sirajuddin, Arlene; Rosing, Douglas R.; Korchin, Borys; Gulley, James L.; Bilusic, Marijo (Frontiers in Oncology, 2020)
The emergence of the SARS-CoV-2 virus has been associated with perplexing clinical sequelae and phenomena that often have no clear link to the underlying infection. There is a wide spectrum of symptoms associated with infection, from minimal respiratory complaints to severe multi-organ failure, often resulting in death. Individuals with malignancies, particularly those whose treatments have left them immunocompromised or immunosuppressed, are among the patient populations thought to be at greater risk for more severe illness. A man with aggressive metastatic chordoma contracted the SARS-CoV-2 virus and was diagnosed with COVID-19 while undergoing intravenous brachyury vaccine immunotherapy. His disease course was remarkably mild, and the virus cleared rapidly. Despite a treatment delay of 3 months due to the COVID-19 pandemic, the patient’s disease has been stable and tumor-related pain has significantly improved. This suggests not only an intact, functional immune system, but also one that appears to have been responsive to cancer treatment. It has been suggested that individuals undergoing treatment for metastatic cancer are at greater risk of severe SARS-CoV-2-related illnesses and complications. While immunosuppression may be a problem, particularly in those receiving conventional chemotherapeutic agents, it is possible that the non-specific effects of immune-enhancing therapies may confer some protection against SARS-CoV-2.